LUNGLAB 3D: VISUALIZATION FOR INTEGRATED SCIENCE LEARNING OF THE HUMAN RESPIRATORY SYSTEM - Annida Fatiya Ananta Sofi; Naili Jauharotun Nisa’; Raihsa Hanipa Naya; Tasbi Khatuz Zumaro; Rahmi Faradisya Ekapti (INSECTA: Integrative Science Education and Teaching Activity Journal, 2026)
Science learning is often perceived as abstract because many concepts are difficult for students to understand concretely, especially the human respiratory system. This often affects students’ motivation and understanding of the concepts being taught. Therefore, innovative and interactive learning media are needed to provide three-dimensional visualizations that make abstract concepts more concrete and engaging. To address this need, a learning medium called LungLab 3D was developed. It is a three-dimensional lung model designed to help students study the human respiratory process in a visual and hands-on way. The media not only illustrates the anatomical structure of the lungs but also demonstrates the mechanisms of inspiration and expiration, enabling students to connect theory with real biological phenomena occurring in the body. This study employed a Research and Development (R&D) approach using the 3D Thiagarajan model (1974), which consists of three main stages: define, design, and development. Product validation was conducted by four junior high school science teachers, assessing six aspects: material relevance, durability, accuracy, efficiency, aesthetics, and safety. The validation results showed an average score of 4.42 with a percentage of 88.3%, categorized as very good. Therefore, LungLab 3D is considered suitable for use in science learning and has the potential to enhance students’ understanding, especially when integrated with creative thematic worksheets that promote exploration and critical thinking.